2011
DOI: 10.1242/dev.067926
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in insect axis formation: two orthodenticle genes and hunchback act in anterior patterning and influence dorsoventral organization in the honeybee (Apis mellifera)

Abstract: SUMMARYAxis formation is a key step in development, but studies indicate that genes involved in insect axis formation are relatively fast evolving. Orthodenticle genes have conserved roles, often with hunchback, in maternal anterior patterning in several insect species. We show that two orthodenticle genes, otd1 and otd2, and hunchback act as maternal anterior patterning genes in the honeybee (Apis mellifera) but, unlike other insects, act to pattern the majority of the anteroposterior axis. These genes regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 62 publications
(93 reference statements)
5
37
0
1
Order By: Relevance
“…Finally, because the function of otd genes on DV patterning in other insects has been reported (Kotkamp et al, 2010;Wilson and Dearden, 2011), I examined the impact of Bm-otd RNAi on DV patterning. However, thus far I have not detected any differences in DV patterning between treated and wild-type embryos.…”
Section: Effects Of Bm-otd Rnai On Dorsal-ventral (Dv) Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because the function of otd genes on DV patterning in other insects has been reported (Kotkamp et al, 2010;Wilson and Dearden, 2011), I examined the impact of Bm-otd RNAi on DV patterning. However, thus far I have not detected any differences in DV patterning between treated and wild-type embryos.…”
Section: Effects Of Bm-otd Rnai On Dorsal-ventral (Dv) Patterningmentioning
confidence: 99%
“…The otd gene is thus considered to be an ancestral anterior patterning gene. In another long germ hymenopteran, Apis mellifera (honeybee), otd1 (Am-otd1) and otd2 (Am-otd2) mRNAs become enriched in the anterior region after fertilization, and both are involved in anterior patterning (Wilson and Dearden, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…in several insect and one spider species (Lehmann and Nüsslein-Volhard 1987;Mito et al 2005;Pultz et al 2005;He et al 2006;Schwager et al 2009;Wilson Maternal expression is not shown. Gap-like expression patterns (i.e.…”
Section: No Indication Of Maternal or "Gap Gene"-like Expression Of Hmentioning
confidence: 99%
“…It appears not to be involved in AP patterning in any other insects. The original patterning system is based on hunchback and orthodenticle in the anterior pole (Schröder 2003 ;Lynch et al 2006a ;McGregor 2006 ;Birkan et al 2011 ;Wilson and Dearden 2011 ). In the posterior region, caudal is a highly conserved determinant, involved in specifying the posterior pole and in posterior axis elongation (see below).…”
Section: Anterior-posterior Patterningmentioning
confidence: 99%
“…The most notable difference from the D. melanogaster pattern is that the distinction between the AP and DV axis patterning systems is not as clear. Indeed, the anterior patterning determinant orthodenticle contributes to DV patterning both in T. castaneum (Kotkamp et al 2010 ) and in the honeybee Apis mellifera (Wilson and Dearden 2011 ). Recent work on DV patterning in the jewel wasp Nasonia vitripennis has shown a conservation of many of the components of the DV gene regulatory network during mid-gastrulation stages (the dorsal gradient; narrow ventral expression domains of cactus , twist , snail , and sim ; lateral expression of brinker ).…”
Section: Dorsoventral Patterningmentioning
confidence: 99%